Symposium 5: Networked Learning: Classroom Experiences at AUT - Sim, Kwong Nui; Kehrwald, Benjamin; Winters, Annemie; Chanane, Nawal; Eberhard, Sally; Nguyen, Nhung (Proceedings of the International Conference on Networked Learning, 2024)
This short paper describes a proposed case study which aims at exploring to what extent Networked Learning enhances classroom experiences at the authors’ institution and how the authors’ institution could adopt networked learning in producing Great Graduates, the authors’ institution mission. The case study is significant with the re-definition of Networked Learning within an institutional context. The study employs an interpretivist research approach (Erickson, 1998) with a combination of direct observation and interview-like methods to understand the experiences of students and teaching academics in on-campus Networked Learning situations among all 15 study options at the authors’ institution. Participants will include volunteered students and academics from various disciplines. The literature review indicates that the adoption of Networked Learning in classroom boosts students’ self-efficacy for social networking and professional development, enhances student-centred experiences with a community focus (e.g., social presence) and provides opportunities for students to further develop their critical thinking. The changing landscape of higher education, especially in this post global pandemic era, warrants the development of a case study approach within a particular context in order to further investigate the adoption of Networked Learning in enhancing teaching and learning processes. The findings will gain insights into achieving the strategic goal of student-directed learning at the authors’ institution and could be applicable to higher education in general in order to improve teaching and learning experiences further. In short, it is an iterative process of developing one’s own Networked Learning application through the affordance of the Networked Learning principles and the practical accomplishment of teaching and learning practices at the course as well as the programme level. Limitations and possible future study are being identified from this proposal.